The impact of climate change on interdependence for microbial genetic resources for agriculture - Beed, Fenton D. (Commission on Genetic Resources for Food and Agriculture, 2011)
Interactions among crops and microbes influence the quality, productivity, and sustainability of food production systems. Microbes, both beneficial and antagonistic, and the array of functions they perform are currently underestimated. Nutrient cycling microbes, endophytes, mycorrhizae, and natural enemies of pests and diseases contribute to durable farming systems, while other microbes are responsible for devastating diseases and toxin contamination of crops. Crops and microbes must therefore be considered together when considering why, and the extent to which, countries are interdependent upon them. In this context, microbial genetic resources (MGRs) are defined as functional units of heredity such as DNA or RNA and do not include biochemical extracts (Glowka 1995).